2019
DOI: 10.1038/s41598-019-51512-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Molecular Fluorophore as a Component of Carbon Dots able to Induce Gelation in a Fluorescent Multivalent-Metal-Ion-Free Alginate Hydrogel

Abstract: We introduce a simple approach to fabricate fluorescent multivalent metal ion-free alginate hydrogels, which can be produced using carbon dots accessible from natural sources (citric acid and L-cysteine). Molecular fluorophore 5-oxo-2,3-dihydro-5H-[1,3]-thiazolo[3,2-a] pyridine-3,7-dicarboxylic acid (TPDCA), which is formed during the synthesis of carbon dots, is identified as a key segment for the crosslinking of hydrogels. The crosslinking happens through dynamic complexation of carboxylic acid groups of TPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…19 Thus, it has been suggested that these aggregates may affect the overall fluorescence properties of a C-dot solution. [29][30][31][32] These findings are consistent with the fact that planar conjugated materials tend to form aggregates in solutions/suspensions. [33][34][35] Self-assemblies of polyaromatic hydrocarbons (PAHs) used as building blocks display PL properties resembling those of C-dots, and the properties of C-dots can be tuned by changing the composition of individual PAH building blocks.…”
supporting
confidence: 86%
“…19 Thus, it has been suggested that these aggregates may affect the overall fluorescence properties of a C-dot solution. [29][30][31][32] These findings are consistent with the fact that planar conjugated materials tend to form aggregates in solutions/suspensions. [33][34][35] Self-assemblies of polyaromatic hydrocarbons (PAHs) used as building blocks display PL properties resembling those of C-dots, and the properties of C-dots can be tuned by changing the composition of individual PAH building blocks.…”
supporting
confidence: 86%
“…In addition, the most common forms of alginate are its gel and polyvalent metal ions, but in practical application, gels without any polyvalent metal ions are welcome [33]. Recently, Kasak et al [34] have prepared polyvalent nonmetal alginate fluorescent hydrogels by dynamic complexing method. Crosslinking occurs through the dynamic complexation of 5-oxo-2, 3-dihydro-5H- [1,3]-thiazolo[3, 2-a] pyridine-3, 7-dicarboxylic acid (TPDCA), carboxylic acid groups in alginate cages and sodium ions (Figure 5).…”
Section: 25mentioning
confidence: 99%
“…Figure5: Schematic diagram of synthesis of crosslinked alginate fluorescent hydrogels. Among them, the picture on the right was shot under the excitation of ultraviolet lamp (reprinted from[34]). …”
mentioning
confidence: 99%
“…In the reaction of citric acid with natural amino acid L-cysteine, 5-oxo-2,3-dihydro-5H- [1,3]-thiazolo [3,2-a]pyridine-3,7-dicarboxylic acid (TPDCA) [42,43] has been synthesized and further applied as a component of fluorescent biodegradable polymers [44,45] and other soft materials [46][47][48][49]. TPDCA also has been identified as a key component for induction of gelation of natural polysaccharide-alginate [50] and related carbon dots [51,52]. In this work, TPDCA was employed as a ligand for the formation of different MOF structures.…”
Section: Introductionmentioning
confidence: 99%